PENGARUH TAYANGAN FASHION DARI INTERNET TERHADAP HASIL BELAJAR DESAIN BUSANA - Elsa Dewi Iriyanti; Siti Mariah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2018)
The purpose of the research is to know (1) the intensityeffect of seeing fashion show from internet to learning result,(2) intensity of viewing fashion show from internet, and(3) learning result. The type of research used ex-post facto.The sampling technique using Simple Random Sampling,with Slovin formula. Data collection by questionnaires anddocumentation methods. Validity used Product Momentand reliability used Cronbach Alpha. Data analysistechnique used descriptiv analysis and hypothesis test usingProduct Moment and it was started by normality andlinearity test. The study shows that (1) there was a positiveand significant between intensity effect of viewing fashionshow from internet and learning result, gave a contributionfashion show from the internet to learning result of 44.5%,while the remaining 55.5% influenced by other factors; (2)the intensity of viewing fashion show from the internet infair categories; (3) learning result in fair category